MEDIA POP-UP BERBASIS KEARIFAN LOKAL : PENDEKATAN KREATIF DALAM PEMBELAJARAN IPAS MATERI INDONESIA KU KAYA BUDAYA INDONESIA DI SD - Shafiyyah, Shafiyyah; Alfina, Rizka; Ningsih, Tri Widia; sabaryati, Johri (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Pop-up book media is designed as a local creative approach to integrate local cultural elements into teaching, thereby increasing students' interest and understanding of the subject matter. The aim of this study is to develop a pop-up book learning medium based on local wisdom in science subject with the material "My Indonesia is Rich in Culture" for fourth grade students of SDN 3 Meninting. The research method used is research and development (R&D) by adapting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The development results show that this local knowledge-based pop-up book medium meets the criteria of validity, practicability and effectiveness based on the results of expert validation, field testing, and qualitative and quantitative data analysis. The use of this media has a positive effect on students' learning engagement and their understanding of local cultural concepts. The evaluation results showed that 85% of students felt that they could better understand Indonesian cultural content after using the media. This study concludes that pop-up book media based on local wisdom is an effective and relevant learning innovation for improving the quality of science education in primary schools.